Pivoting in startups: a judgment based approach - Chaparro, Ximena Alejandra Flechas (2022)
The theme of this thesis is pivoting in startups from an entrepreneurial judgment approach. By pivoting (or pivot decision), we refer to a strategic decision made after a failure (or the identification of potential failure) of one or more elements of the current business model, which potentially threatens the startups resource base. This decision may change the course of action, reconfigure the resource basis, and modify the opportunity belief and one or more elements of the business model. Despite the pivot being recognized among practitioners as one of the most crucial decisions during the new venture creation, this topic has scarcely been studied in academic research. There are five important aspects that remain unclear. First, there is not yet a clear definition of what pivoting is and how it differs from other strategic decisions. Second, it has not been examined which cognitive-affective attributes and biases may affect judgment during pivoting. Third, it is still unknown how the elements affecting the judgment during this decision (failures, beliefs, actions) intertwine to lead to pivots. Fourth, there is a lack of understanding of how failures relate to pivots and why some entrepreneurs decide to pivot, whilst others persist regardless of failures emergence. Finally, it is not clear whether pivots occur differently and how they differ from each other. The identification of these gaps led to the formulation of the following research question: How do entrepreneurs pivot their startups? To address this question, this study adopts a rich methodological approach that combines systematic literature reviews and empirical qualitative research, following a processual approach based on case studies. A total of 39 pivot decisions were analyzed. Such decisions occurred in 24 startups: 5 Colombian, 18 Brazilian, and 1 British. The systematic literature reviews identified the main cognitive aspects involved in pivoting, the perspective streams studying this decision, and we established a refined definition for pivoting in startups. Based on the empirical studies, we developed a process model showing how a series of interrelated events results in pivots. This study also found out that the interplay between the perception of failure and attribution of failure plays a major role in determining whether the entrepreneurs will update their beliefs and pivot, or rather, will reinforce their beliefs and persist. Furthermore, based on the analyses, four events were identified to be critical in explaining pivot decisions: actuating response, abandonment of initial belief, retrospective sensemaking, and prospective sensemaking. Finally, three major pivot approaches were identified: break-point, parallel, and adaptative. The findings contribute to the entrepreneurial judgment literature by providing a better understanding of the influence of failure (perceptions and attributions) on entrepreneurs beliefs and further actions. Additionally, were identified theoretical and practical implications and opportunities for further research. We hope that the findings of this study will increase awareness about how challenging and resource-consuming pivot decisions can be. Moreover, we expect this study can serve as a supplement for entrepreneurs, mentors, teachers, and others involved to better guide pivot decisions.